1997
DOI: 10.1046/j.1365-2958.1997.4431808.x
|View full text |Cite
|
Sign up to set email alerts
|

Nascent membrane and presecretory proteins synthesized in Escherichia coli associate with signal recognition particle and trigger factor

Abstract: SummaryThe Escherichia coli signal recognition particle (SRP) and trigger factor are cytoplasmic factors that interact with short nascent polypeptides of presecretory and membrane proteins produced in a heterologous in vitro translation system. In this study, we use an E. coli in vitro translation system in combination with bifunctional cross-linking reagents to investigate these interactions in more detail in a homologous environment. Using this approach, the direct interaction of SRP with nascent polypeptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
187
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(200 citation statements)
references
References 40 publications
13
187
0
Order By: Relevance
“…It is, therefore, possible that many proteins move into the SecA/SecB pathway from SRP, and that these two pathways are not mutually exclusive. Consistent with this notion, PhoE utilizes a SecB-dependent pathway, yet the PhoE signal sequence has been found to crosslink with SRP upon readdition of wild-type lysate in a heterologous expression system [22] or when Ffh is added to physiological concentration in a homologous expression system [9]. In addition, some of the PhoA signal sequences, which are shown here to be sensitive to Ffh depletion, have also been shown to accumulate in the absence of SecB [12] and SecA [23] in vivo.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…It is, therefore, possible that many proteins move into the SecA/SecB pathway from SRP, and that these two pathways are not mutually exclusive. Consistent with this notion, PhoE utilizes a SecB-dependent pathway, yet the PhoE signal sequence has been found to crosslink with SRP upon readdition of wild-type lysate in a heterologous expression system [22] or when Ffh is added to physiological concentration in a homologous expression system [9]. In addition, some of the PhoA signal sequences, which are shown here to be sensitive to Ffh depletion, have also been shown to accumulate in the absence of SecB [12] and SecA [23] in vivo.…”
Section: Resultsmentioning
confidence: 79%
“…The substrate speci¢city of SRP for membrane proteins may re£ect the higher a¤nity of SRP for relatively hydrophobic signal sequences. Consistent with this idea, in vitro crosslinking studies have shown that more hydrophobic signal sequences are better crosslinked to Ffh [9,10]. Furthermore, crosslinking to trigger factor was unaffected by hydrophobicity [9].…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Strain MC4100 was used to obtain S135 lysate. Plasmid pBSKftsQ was constructed by ligating the BamHI/HindIII fragment of pNB1 (21) into BamHI/HindIII-cut pC4meth101FtsQ (22).…”
Section: Methodsmentioning
confidence: 99%